Reconstructing J. L. Austin’s Method: ‘Linguistic Phenomenology’ as a Technology of Philosophical Research - S. N. Kasatkin (Омский научный вестник: Серия "Общество. История. Современность")
This article is aimed at an (updated) reconstruction of the method of philosophical research proposed by the prominent British analytical philosophers, John Langshaw Austin (1911–1960) — a study of what we (should) say when and why — alternative to its ‘canonical’ (and debatable) account, given more than half a century ago by Austin’s colleague and editor, James Urmson. Resting on a wider range of sources, the article, first, presents the Austin’s method as a practical technology, second, reformulates its intention and structure based on the key attitudes of the British thinker (the ideas of ‘strict’ philosophy and ‘linguistic phenomenology’), third, localizes the methodical components associated with them by the author. As a result, the Austin’s method is revealed by means of three research stages (goal setting, formation of an empirical database and its theoretical explanation) with their inherent tasks, procedures, techniques and methodical guidelines. Some related limitations of the author’s method are also fixed, first of all, its focus not so much on creating a ‘high’ philosophical ‘theory’, as on ensuring a greater rigor, factual rootedness and thereby usefulness of philosophical reasoning.